Academic writing conventions in English-medium linguistics journals in Italy : Continuity and change over the last 30 years - Bondi, Marina; Nocella, Jessica Jane (Jan Kochanowski University Press, 2023)
Against the background of studies on “academic Englishes”, this paper is a study parallel to Dontcheva-Navratilova (this issue). Focusing on the use of English in Italian academic publishing and on English linguistics in particular, we look at the development of academic writing conventions in research articles written by Italian scholars over the last 30 years. The study is based on a small corpus of 20 single-authored English-medium research articles – ten representing the period from 1990 to1995 and ten from between 2014 and 2019 – published in the official journal of the Italian association of Anglicists (Textus) and in the applied linguistics journal Rassegna Italiana di Linguistica Italiana (RILA). The study draws on genre analysis to explore possible changes in rhetorical structure and on corpus analysis to study forms of self-mention. Special attention is paid to introductions, methodology, and conclusions. The results show diachronic changes both at a macrolevel in rhetorical structure with a clearer IMRAD structure and a more empirical methodology in the second phase, while at a microlevel forms of self-mention show a marked increase in non-personal and implicit (locational) self-mention. This seems to respond to the tension between personal and impersonal forms that has largely characterized the development of the genre in English as well as to the contact between different academic cultures.